Effects of Chronic and Experimental Acute Masseter Pain on Precision Biting Behavior in Humans - Al Sayegh, Samaa; Borgwardt, Annie; Svensson, Krister G.; Kumar, Abhishek; Grigoriadis, Anastasios; Christidis, Nikolaos (Frontiers in Physiology, 2019)
Chronic pain in the orofacial region is common worldwide. Pain seems to affect the jaw motor control. Hence, temporomandibular disorders (TMD) are often accompanied by pain upon chewing, restricted mouth opening and impaired maximal bite forces. However, little is known on the effects of pain, in particular the effects of chronic jaw muscle pain on precision biting. The aim of the study was to investigate the effect of chronic and acute jaw muscle pain on oral motor control during precision biting in humans. Eighteen patients with chronic masseter muscle pain and 18 healthy participants completed the experiment. All participants were examined according to the Diagnostic Criteria for TMD. Experimental acute pain was induced by bilateral, simultaneous sterile hypertonic saline infusions into the healthy masseter muscles. A standardized hold and split biting task was used to assess the precision biting. The data was analyzed with non-parametric statistical tests. The results showed no significant differences in the hold forces, split forces, durations of split or peak split rates within or between the pain and pain-free conditions. The mean split rate increased significantly compared to baseline values both in the chronic patients and the pain-free condition. However, this increase was not evident in the experimental acute pain condition. Further, there were no significant differences in the mean split rates between the conditions. The data suggest that jaw muscle pain does not seem to alter precision biting in humans, however, the possibility that a nociceptive modulation of spindle afferent activity might have occurred but compensated for cannot be ruled out.